Gulp : adventures on the alimentary canal - Roach, Mary (W.W. Norton, 2013)
Few of us realize what strange wet miracles of science operate inside us after every meal. In her trademark style, Mary Roach investigates the beginning, and end, of our food, addressing such questions as why crunchy food is so appealing, how much we can eat before our stomachs burst, and whether constipation killed Elvis.